2009
DOI: 10.1007/s10566-009-9086-6
|View full text |Cite
|
Sign up to set email alerts
|

End-of-Life Issues in US Child Life Specialist Programs

Abstract: A professional outlet in most children's hospitals for seriously-ill children is the child life specialist. Our objective in this study was to determine the extent that dying and death is emphasized in child life programs in the United States. Therefore, we surveyed via snail mail the 35 child life programs on the website of the Child Life Council. A response rate of 74% revealed that all programs offer something on this topic and over twothirds have a separate course for the topic of dying and death, with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Return rates were 79% from medical schools (N = 99), 71% from nursing schools (N = 410) (Dickinson, 2007), 90% from dental schools (N = 52) (Sirmons, Dickinson, & Burkett, 2010), 74% from child life programs (N = 26) (Parvin & Dickinson, 2010), and 100% from veterinary medicine schools (N = 28) (Dickinson, Roof, & Roof, 2011). With the exception of dental schools (58%), over 96% of the various professional schools offered "something" on end-of-life issues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Return rates were 79% from medical schools (N = 99), 71% from nursing schools (N = 410) (Dickinson, 2007), 90% from dental schools (N = 52) (Sirmons, Dickinson, & Burkett, 2010), 74% from child life programs (N = 26) (Parvin & Dickinson, 2010), and 100% from veterinary medicine schools (N = 28) (Dickinson, Roof, & Roof, 2011). With the exception of dental schools (58%), over 96% of the various professional schools offered "something" on end-of-life issues.…”
Section: Resultsmentioning
confidence: 99%
“…This emphasis in child life indicates the importance of the topic of dying, death, and bereavement in child life educational programs. One child life respondent stated (Parvin & Dickinson, 2010): I can't imagine not having this be a required part of educational preparation for child life specialists. In talking with students, I've found that this topic by far creates the most anxiety in regard to future clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have found that children and adolescents with chronic diseases tend to have more psychological problems when compared with healthy children and adolescents (Carter, 2014;Doka, 1996;Litt et al, 1982;Parvin & Dickinson, 2010). Rollins and colleagues (2018) found that the potential effects of chronic illness or disabilities for adolescents increase their sense of feeling different from their peers, limit job or career opportunities, increase concern about why they have the disorder, limit opportunities for heterosexual friendships, decrease their abilities to master their medical self-care, and lead to difficulty with the transition from the pediatric to adult unit.…”
Section: Stressors Due To Chronic And/or Life-threating Diseasesmentioning
confidence: 99%
“…Specifically, pediatric patients with chronic disease respond to strict treatment regimens with regressive and dependent reactions, aggressive nonadherence, and impaired self-esteem (Doka, 1996;Rollins et al, 2018). In addition, adolescents may begin to fear that their life span could be limited by chronic disease or death (Parvin & Dickinson, 2010;Rollins et al, 2018).…”
Section: Stressors Due To Chronic And/or Life-threating Diseasesmentioning
confidence: 99%
See 1 more Smart Citation